KEANEKARAGAMAN HAYATI DAN ROSOT KARBON PADA RAWA-GAMBUT DI BUKIT BATU, KABUPATEN BENGKALIS, PROVINSI RIAU (Biodiversity and Carbon Sinks on Peat Swamps in Bukit Batu, Bengkalis Regency, Riau Province) - N. M. Heriyanto; Dolly Priatna; Ismayadi Samsoedin (Jurnal Penelitian Hutan Tanaman, 2020)
ABSTRACTResearch on biodiversity and carbon sinks is still needed by the government to support policies in order to manage forests sustainably. The purpose of this study was to analyze the composition of species, stand structure, biomass and carbon sinks on peat-swamps in Bukit Batu, Bengkalis Regency, Riau Province. The research method was carried out with an inventory of vegetation to determine the potential of stands, rejuvenation, biomass and carbon sinks. Sample plots were taken randomly in the form of measuring plots of 100 m x 100 m in each condition of old secondary forest, young secondary forest and old scrub forest in the peat-swamp protection forest. The species commonly found and evenly spread in all conditions of the peat-swamp forest were Gymnacranthera paniculata, Shorea teysmanniana, and Shorea gibbosa. The structure of the third stand condition of the peatswamp forest was still like a peat-swamp natural forest with the structure of the curve was in the shape of an inverted letter “J.” The three conditions of the peat-swamp forests have high biomass and carbon deposits with the highest content of those that were found in the old secondary forests, and the lowest was in the old scrub forests. The condition of the old secondary  forests has the highest potential to absorb carbon dioxide in the air. The tree species that are potentially used as seed sources were S. teysmanniana, S. gibbosa and Diospyros maingayi.                                                   ABSTRAK                                                               Penelitian keanekaragaman hayati dan rosot karbon masih diperlukan pemerintah untuk mendukung kebijakan dalam rangka mengelola hutan secara berkelanjutan. Tujuan penelitian ini adalah untuk menganalisis komposisi jenis, struktur tegakan, biomassa dan rosot karbonnya pada rawa-gambut di Bukit Batu, Kabupaten Bengkalis, Provinsi Riau. Metode penelitian dilakukan dengan cara inventarisasi vegetasi guna mengetahui potensi tegakan, permudaan, biomassa dan rosot karbon. Sampel plot diambil secara acak berupa plot berukuran 100 m x 100 m di setiap kondisi hutan sekunder tua, hutan sekunder muda dan hutan belukar tua pada hutan lindung rawa-gambut. Jenis Gymnacranthera paniculata, Shorea teysmanniana dan Shorea gibbosa ditemukan tersebar merata di setiap kondisi hutan rawa-gambut. Struktur tegakan ketiga kondisi hutan rawa-gambut masih seperti hutan alam rawa-gambut dengan kurva struktur tegakan berbentuk huruf “J” terbalik. Ketiga kondisi hutan rawa-gambut tersebut memiliki biomassa dan simpanan karbon yang tinggi dengan biomassa dan simpanan karbon tertinggi ada di hutan sekunder tua dan terendah di hutan belukar tua. Kondisi hutan sekunder tua berpotensi untuk menyerap karbon dioksida di udara yang tertinggi. Pohon yang potensial dijadikan sumber benih adalah pohon S. teysmanniana, S. gibbosa, dan Diospyros maingayi.